TYPOLOGY OF VILLAGE GOVERNANCE ASSESSED BASED ON SOCIOLOGICAL PERSPECTIVE - Flambonita, Suci (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Along with modern developments that exist today, various polemics have emerged in determining the typology of village governance that is in accordance with the principles of legal policy (legal policy) related to the sociological foundation in the form of understanding village conditions is absolutely necessary. Therefore, a stronger State institution is needed in dealing with the rational division of tasks and authorities between the State and regions (villages). In its preparation, it is necessary to describe a sociological condition of an intact village, which is viewed from the village elements which include the village area, village life system and village administration. The method and approach used was empirical (sociological research). There were several arguments for the need to understand the condition of the village sociologically where various villages throughout Indonesia have always been the basis of community livelihoods that have autonomy in managing the governance of the population, local institutions and economic resources with all the local wisdom possessed by local Indonesian communities. Furthermore, the regulation on village governance is intended to respond to the globalization process marked by the liberalization process of information, economy, technology, culture, etc.